Effects of different lipoprotein apheresis methods on serum protein levels. (May 2015) - Julius, U.; Siegert, G.; Kostka, H.; Schatz, U.; Hohenstein, B.
Abstract: Background: A total plasma exchange was the first extracorporeal method to treat patients with severe hypercholesterolemia. But in the long run it has several disadvantages. The newer lipoprotein apheresis (LA) methods claim to be more selective with respect to the removal of atherogenic lipoproteins and thus are supposed to avoid an additional protein loss. Methods: We wanted to compare the effect of these methods on serum protein concentrations (total serum protein, albumin, proteins measured with electrophoresis, immunoglobulins, fibrinogen, transferrin, and ferritin) which were checked before and after a single LA session in 75 patients. All patients underwent active LA treatment using 6 different LA methods (HELP, TheraSorb ® LDL, DALI, Lipidfiltration, Liposorber D, MONET). Post-apheresis concentrations were corrected for changes in hematocrit. Results: The slightest impact on total serum protein was observed with the whole-blood methods. Liposorber D showed the least reduction of albumin levels. All LA methods had a small effect on alpha1-globulins and beta-globulins, but alpha2-and gamma-globulins were reduced to a different extent. A major effect was seen on the immunoglobulins when filtration methods were applied. In the patients treated with MONET, both pre- and post-apheresis Immunoglobulin M concentrations were below the normal range. HELP and the filtration methods significantly reduced the fibrinogen concentrations. The filtration methods also decreased ferritin levels but the post-apheresis ferritin levels were still in the normal range. Conclusion: All LA methods had an influence on protein concentrations. At present, these findings will not yield an individualized treatment approach for any selective LA method due to the lack of prospective comparative studies. At minimum, special attention should be paid to protein concentrations in patients suffering from protein deficit.